PENGARUH MEDIA FILM ANIMASI PENDEK TERHADAP KEMAMPUAN MENULIS TEKS NARASI (CERITA IMAJINASI) SISWA KELAS X SMA SWASTA RAHMAT ISLAMIYAH MEDAN - Tobi Bagustian Tanjung; Syamsuyurnita Syamsuyurnita (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
This study aims to determine the ability to write narrative texts of class X students of SMA Rahmat Islamiyah Medan. This type of research is quantitative research with a Quasi Experimental Design approach. The data collection technique is the test. The data analysis technique used was a paired simple test with a different test. The results of this study, namely: that from the results of the pretest test that has been obtained by class X SMA Rahmat Islamiyah Medan with an average pretest score of 71.14% and an average posttest score of 82.03%. The calculation of the t-test on the posttest tcount (48,836) > ttable (2,052) which means that there is an average difference in the posttest and pretest scores. The increase in pretest-posttest is 11%, which means that the working hypothesis (Ha) in this study is accepted and the null hypothesis (Ho) is rejected.